ANALISIS PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI KALIMANTAN BARAT - SIDABUTAR B01108109, CHRISTINE LAURA (Jurnal Pembangunan dan Pemerataan, 2014)
The thesis entitled â€œAnalysis of Revenue and The General Allocation Fund Against Economic Growth in West Kalimantan Provinceâ€. The purpose of this study was to analyze the influence of Revenue and the General Allocation Fund on economic growth districts or cities in West Kalimantan. This study uses quantitative methods, namely by processing secondary data which is then carried out an analysis of the research object in accordance with the research objectives. That the data used are secondary data period 2009-2011 are sourced from the Bureau of Government Financial Blood West Kalimantan and Central Bureau of Statistics. From the research it is known that the revenue can have a positive impact 0.004594 on economic growt districts or cities in West Kalimantan, while the average of the general allocation fund is â€œbig oneâ€ region is sold to be a significant impact on regional economic growth districts or cities in West Kalimantan. Keywords: Revenue, the General Allocation Fund, Economic Growth